Efficacy and Safety of Perioperative Immunotherapy for Patients with Non-Small Cell Lung Cancer: A Systematic Review and Network Meta-Analysis - Zhijuan Du; Siyuan Chen; Yuhui Qin; Yahui Lv; Xiangyu Du; Heying Yu; Zhefeng Liu (Current Oncology)
Background: The objective of this study is to indirectly compare the efficacy and safety of all currently available neoadjuvant chemoimmunotherapy and perioperative chemoimmunotherapy in randomized controlled trials (RCTs) involving patients with resectable non-small cell lung cancer (NSCLC) to identify optimal treatment regimens. Methods: Eligible studies evaluating neoadjuvant chemoimmunotherapy and perioperative chemoimmunotherapy-based regimens in resectable NSCLC patients were included. Clinical outcomes were extracted for event-free survival (EFS) and overall survival (OS), as well as the incidence of pathological complete response (pCR), major pathological response (MPR), any-grade adverse events (AEs), and treatment-related adverse events (TRAEs) in the Bayesian framework. A subgroup analysis of EFS was conducted according to PD-L1 expression, histological type and reaching pCR or not. Results: We selected eight RCTs involving 3113 patients. Our analysis found no significant differences between perioperative immunotherapy and neoadjuvant immunotherapy in terms of MPR (RR 0.72, 95% CI 0.39 –1.3), pCR (RR 0.73, 95% CI 0.24–2.3), EFS (HR 0.95, 95% CI 0.56–1.7), and OS (HR 95% CI 3.9–4.2). Subgroup analyses revealed that neoadjuvant immunotherapy demonstrated superiority in the programmed death-ligand 1 (PD-L1) high-expression cohort, the non-squamous cell carcinoma cohort, and the non-smoking cohort. Conversely, perioperative immunotherapy ranked first in the PD-L1 low-expression cohort, squamous cell carcinoma cohort, and non-pCR cohort. Conclusions: Our findings indicate that neoadjuvant immunotherapy and perioperative immunotherapy exhibit comparable efficacy in patients with NSCLC. These results provide valuable evidence for guiding the treatment of patients with resectable NSCLC.